Chain gangs, roads, and reform in North Carolina, 1900-1935 - Thomas, Susan W. (2011)
For the first three decades of the twentieth century, dozens of predominantly black county chain gangs proliferated across North Carolina. The camps existed solely to build county roads, a consequence of efforts by the North Carolina Good Roads Association (NCGRA) to create a network of reliable roads in order to improve the state's economic prospects. As a self-proclaimed progressive non-governmental group, the NCGRA promoted reliance on chain gang labor as a reform that would profit the state and uplift the convicts. While convicts built roads that helped position North Carolina at the forefront of economic progress in the South, rather than benefitting the prisoners, the chain gangs became sites of abuse and degradation. Chain gang convicts often resisted the inhumane conditions they endured, relying heavily on their connection to the State Board of Charities and Public Welfare (SBC), a state agency whose official duties included inspecting penal institutions and making recommendations for their improvement. With the SBC's assistance, convicts pushed for investigations into the camps and conveyed their messages to powerful politicians and newspapermen who publicized their struggle. Convicts helped shape reformers' debates as they risked severe punishment and even death by engaging in protest and resistance against the brutality of the camps. By the 1930s, their pursuit of humane treatment came to influence state level efforts to rectify the abusive conditions so long associated with the county chain gangs